LEARNING IN DELIBERATIVE DEMOCRACY - Hidayat, Melda Fadiyah (Prodi Ilmu Pemerintahan FISIP UNIBBA, 2019)
Democracy in Indonesia is often carried out with the word “election”. But democracy is not just the word “election”, democracy has wide and many phenomena and reviews these phenomena are important. One of them is deliberative democracy. Many scientists have reviewed this idea. Both from the forum, both from the process, both from the of participants, both from the ideas themselves in Indonesia. Even though deliberative democracy has other elements. One of them is learning. It's very rare to hear the idea of learning in deliberative democracy itself. Rarely describe what learning is and why it is important. And it turns out learning has an important role in supporting the deliberate process in the public sphere / public space